Postoperative Relief and Complications in Eagle’s Syndrome: A Retrospective Analysis - Ikbal, Ashik; Haque, Muhammad Mahmudul; Shahrear, Md Khaled (Journal of Rangpur Medical College, 2025)
Introduction: Eagle’s Syndrome (ES) is a rare clinical condition characterized by symptomatic elongation of the styloid process or calcification of the stylohyoid ligament. Objective: The objective of the study was to evaluate postoperative symptom relief and complication rates following styloidectomy in patients with radiologically confirmed Eagle’s Syndrome. Methods: A retrospective review was conducted on 90 patients diagnosed with ES and treated surgically at a tertiary center in Bangladesh. Demographic data, symptom profiles, surgical approaches, and postoperative outcomes were analyzed. Symptom relief was assessed using the visual analog scale (VAS), and complications were recorded. Correlation between symptom duration and postoperative improvement was calculated. Results: Most patients were female (60%) and aged 46–60 years (40%). Throat pain (80%) and dysphagia (53.3%) were the predominant presenting symptoms. Intraoral styloidectomy was performed in 66.7% of cases. Complete relief was observed in 83.3% for throat pain, 80% for otalgia, and 72.9% for dysphagia. Complications were low (18.9%), with transient dysphagia (6.7%) and wound infection (5.6%) being most common. A significant correlation was found between shorter symptom duration and greater relief (r=0.9999, p=0.0107). Conclusion: Surgical management of Eagle’s Syndrome yielded high symptom resolution and minimal complications, particularly when intervention was timely. Early diagnosis was crucial for optimal outcomes. J Rang Med Col. 2025 Sep;10(2): 109-114